(untitled) (Reflection and Critique Law Magazine, 2022)
Brazil occupies a prominent role within the foreign policy of Latin America and is considered a potential regional political leader at the international level. This process stems from a long historical tradition of its foreign policy that has always been active, even within the perspective of a soft power policy. Thus, in a comparative analysis with Argentina, which also has a strong influence on international politics, this work aims to make a historical digression regarding the construction of the identity of the foreign policy of Brazil and Argentina, the two largest MERCOSUR member states, and It also addresses how these historical factors and current interests will affect the direction of MERCOSUR and, consequently, Latin America’s foreign policy. Key words: foreign policy, Brazil, Argentina, MERCOSUR.